2017
DOI: 10.1002/jbio.201700004
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation leads to enhanced radiosensitivity through induction of apoptosis and autophagy in human cervical cancer cells

Abstract: The radiomodulatory effect of photobiomodulation (PBM) has recently been studied in cancer cells. The aim of this study was to investigate cellular mechanisms involved in the X-ray radiosensitivity of HeLa cells pre-exposed to PBM. HeLa cells were irradiated with 685 nm laser at different energy densities prior to X-ray ionizing radiation. After irradiation, clonogenic cell survival, cell death due to apoptosis and autophagy were determined. Levels of intracellular reactive oxygen species (ROS), DNA damage and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 54 publications
0
20
0
1
Order By: Relevance
“…But the role of autophagy in radioresistance is still controversial. Wang et al (2013) hold the view that autophagy promotes radioresistance in pancreatic cancer cells, while Djavid et al (2017) concluded that the mobilization of autophagy could cause cell death through lysosomal activation, thus causing an enhancement of radiosensitivity in human cervical cancer cells. Our study demonstrated that autophagy inhibition increased the radiosensitivity of NPC cells and that there was a positive correlation between autophagy and radioresistance.…”
Section: Discussionmentioning
confidence: 99%
“…But the role of autophagy in radioresistance is still controversial. Wang et al (2013) hold the view that autophagy promotes radioresistance in pancreatic cancer cells, while Djavid et al (2017) concluded that the mobilization of autophagy could cause cell death through lysosomal activation, thus causing an enhancement of radiosensitivity in human cervical cancer cells. Our study demonstrated that autophagy inhibition increased the radiosensitivity of NPC cells and that there was a positive correlation between autophagy and radioresistance.…”
Section: Discussionmentioning
confidence: 99%
“…showing apoptotic signs after 20 min treatment with 20 J/cm 2 (Djavid et al, 2017). At the same time, other cancer cell lines demonstrated much more intensive proliferation as a result of light exposition.…”
mentioning
confidence: 94%
“…The PBM effect is also strongly dependent on the cell type: different cell lines demonstrate different responses to light irradiation . In particular, several studies showed that PBM can stimulate proliferation in some cell lines and cell death in others . For example, red and near infrared (NIR) light stimulate proliferation of human adipose‐derived stem cells and, at the same time, can effectively inhibit proliferation of fibroblasts .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, NIR light was shown to significantly induce caspase‐3 activation and promote apoptosis in pancreatic cancer cells . It was also reported that both visible and infrared light demonstrated cytotoxic effects on human breast cancer cells , and lead to boosted radiosensitivity through enhancement of apoptosis in HeLa cells . As a result, low power laser irradiation in combination with radiotherapy can decrease the delivered radiation dose and, consequently, prevent some radiotherapy related side effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation